Perbaikan Beberapa Sifat Kimia pada Tanah Pasca Tambang Batubara dengan Pemberian Dosis Bokashi Kiapu (Pristia stationes L.) dan Krinyu (Choromolaena odorata L.) - Muhammad Fahrul; Rabiatul Jannah; Patmawati Patmawati (Mulawarman University, 2019)
The purpose of this study was to determine the nutrient content of bokashi fertilizers that matched the SNI compost quality standards and the best bokashi and chrysanthemum mixture dosages and the effect of increasing the best chemical status on post-coal mine soil. This research was conducted for two 2 months. The land for this research was taken from post-coal mine land in the Loa Bakung area, Samarinda. The place for conducting research is carried out on Jl. Jakarta Blok BN No 36. Loa Bakung, Samarinda. The method used in this study is descriptive and comparative. This research has 2 stages, namely the first stage of making bokashi kiapu and krinyu mixture and the second stage of the incubation process of post-coal mine soil with a treatment dose that is soil without bokashi, soil with a dose of bokashi 17.5 g polybags, 20 g polybags and 22.5 g polybags, each repeated 3 times. Then analyzed at the Soil Science Laboratory, Mulawarman University Faculty of Agriculture, with parameters pH, C/N ratio, C-organic, N, P, K. Bokashi analysis data based on 2004 SNI Compost Quality Standards and soil analysis data based on soil chemical review status which was developed by the Bogor Soil Research Center in 2009. The results of this study showed that the bokashi mixture of kiapu and krinyu had an effect on increasing soil chemical properties in post-coal mine land, the status of bokashi according to SNI, 22.5% organic C had not matched the quality standard, pH 8.87 not yet according to quality standards, N 1.86% according to quality standards, C/N 12.11 according to quality standards, P 0.98 ppm according to quality standards, and K 2.11 ppm according to quality standards. The best application is at a dose of 22.5 g polybags with a rise at week 4, namely pH 4.94 with acidic status, organic C 2.71% with moderate status, N 0.16% with low status, C/N ratio 16 , 08 with high status, P 31.85 ppm with high status, and K 120.41 ppm with very high status.